Vilken granplanta bör användas vid föryngring? - Oleinikoff, Patrik (2018)
The purpose of this study is to compare suppliers and variation of spruce seedlings that Linköpings Skogstjänst AB often uses in the rejuvenation phase. A trial plot has been laid out in the fields where seven different plants have been compared. A comparison has also been made between the bare root seedling and containerized seedlings. The parameters that have been measured and investigated are the growth, survival and protection of plants against the weewil. The bare root seedling had clearly higher survival than the containerized seedlings which was predicted before the attempt was made. The chemically treated plants seemed to keep the protection better against the weevil than the wax-treated plant, especially year two. The containerized seedlings delivered were smaller than the bare root seedling, but showed a higher growth and grew better under the first two years compared to the bare root plants.